LncRNA MALAT1 regulates growth of carcinoma of the lung through modulating miR-338-3p/PYCR2 axis: LncRNA MALAT1 regulates lung cancer - Geng, Yang; Chen, Pengfei; Zhang, Lei; Li, Xiaojun; Song, Chao; Wei, Xueting; Gong, Huiyuan (Cellular and Molecular Biology, 2023)
The progression of several cancers, including lung cancer, has been linked to long non-coding RNAs (lncRNAs) (LC). The current research concentrated on elucidating the effects of MALAT1 on the course of LC and investigating potential pathways. The qPCR and in situ hybridization (ISH) assays were used to measure MALAT1 expression in LC tissues. Additionally, the overall survival (OS), a percentage of LC patients with various MALAT1 levels was examined. Additionally, it was determined whether MALAT1 was expressed in LC cells through qPCR analysis. LC cells' proliferation, apoptosis, and metastasis were all examined concerning MALAT1 utilizing the following techniques: EdU, CCK-8, western blot and flow cytometry. This study predicted and verified the correlation between MALAT1, microRNA (miR)-338-3p as well as pyrroline-5-carboxylate reductase 2 using bioinformatics and dual-luciferase reporters (PYCR2). On the activity and function of MALAT1/miR-338-3p/PYCR2 in LC cell activities, more study was conducted. The amount of MALAT1 was raised in LC tissues and cells. Low OS was seen in patients with elevated MALAT1 expression. By inhibiting MALAT1, LC cells saw decreased migration, invasion, and proliferation as well as an increase in apoptosis. Additionally, PYCR2 appeared as an objective of miR-338-3p, while MALAT1 was a target of miR-338-3p. Additionally, the over-expression of miR-338-3p had effects that were comparable to those of MALAT1 down-regulation. The function of miR-338-3p inhibitor on the functional activities of LC cells co-transfected with sh-MALAT1 was partially recovered by PYCR2 inhibition. MALAT1/miR-338-3p/PYCR2 maybe the novel target for LC therapy.